Spermidine/spermine N1-acetyltransferase-mediated polyamine catabolism regulates beige adipocyte biogenesis - Yuan, Fang (Metabolism, 2018)
OBJECTIVE: Cold and β3-adrenergic receptor (AR) agonists activate beige adipocyte biogenesis in white adipose tissue (WAT). The two stimuli also induce expression of inflammatory cytokines in WAT. The low-grade inflammation may further promote WAT browning. However, the mechanisms to reconcile these two biological processes remain to be elucidated. In this study, we aim to investigate the roles of the rate-limiting polyamine catabolic enzyme spermidine/spermine N1-acetyltransferase (SAT1) in regulating beige adipocyte biogenesis and inflammation. METHODS: Adipose-specific SAT1 knockout mice (SAT1-aKO) were generated by crossing adiponectin-cre to SAT1-lox/lox mice. Metabolic phenotype was investigated. Primary preadipocytes were isolated from inguinal WAT (iWAT) and differentiated to adipocytes for studying beige adipocyte biogenesis. RESULT: The expression and enzymatic activity of SAT1 were up-regulated in iWAT upon cold and β3-AR stimulation. SAT1-aKO mice developed late-onset obesity on a high-fat diet with impaired cold-induced beige adipocyte biogenesis and energy expenditure. RNA-seq analysis of iWAT from cold-challenged SAT1-aKO mice revealed that, in addition to beige adipocyte biogenesis signatures, the immune response markers were highly enriched among reduced genes. In cultured adipocytes, SAT1 overexpression or pharmacological activation with N1, N11-diethylnorspermine (DENSpm) elevated oxygen consumption and increased the expression of beige adipocyte marker UCP1 and PGC-1α. DENSpm treatment of adipocytes also increased the expression of inflammatory genes. SAT1 activation enhanced hydrogen peroxide production in adipocytes. Antioxidant N-acetylcysteine abrogated the elevated UCP1 expression and reversed some inflammatory genes induced by SAT1 activation. CONCLUSIONS: SAT1 activation plays a key role in cold and β3-AR agonist-induced beige adipocyte biogenesis and low-grade inflammation.